2012
DOI: 10.1007/s10570-012-9682-8
|View full text |Cite
|
Sign up to set email alerts
|

Layer by layer complex architectures based on ammonium polyphosphate, chitosan and silica on polyester-cotton blends: flammability and combustion behaviour

Abstract: Hybrid organic-inorganic coatings containing ammonium polyphosphate (APP), chitosan and silica have been deposited on polyester-cotton blends (PET-CO), exploiting the layer by layer assembly. To this aim, two different complex architectures (namely, chitosan/APP bilayers plus silica/ silica bilayers or silica/silica/chitosan/APP quadlayers) have been thoroughly investigated. The effect of their morphologies on the flame retardancy properties of the fabrics (flammability and combustion behaviour) has been asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 12 publications
(10 reference statements)
1
65
2
1
Order By: Relevance
“…The first attempt has been made by depositing complex architectures made of chitosan, ammonium polyphosphate and silica nanoparticles bearing positive or negative charge on cotton-PET blends [101]. Such coating constituents have been selected on the basis of the results achieved by silica/silica coatings and chitosan/ ammonium polyphosphate coatings described in the previous paragraphs.…”
Section: Coating Constituents Main Results Referencementioning
confidence: 99%
“…The first attempt has been made by depositing complex architectures made of chitosan, ammonium polyphosphate and silica nanoparticles bearing positive or negative charge on cotton-PET blends [101]. Such coating constituents have been selected on the basis of the results achieved by silica/silica coatings and chitosan/ ammonium polyphosphate coatings described in the previous paragraphs.…”
Section: Coating Constituents Main Results Referencementioning
confidence: 99%
“…The first example of an LbL hybrid coating consisted of chitosan, ammonium polyphosphate, and silica nanoparticles (bearing positive or negative charges) deposited on cotton-PET blends [112]. It was found that the morphology and the physical stability of the assemblies play a key role in determining the fire performance of the treated substrates.…”
Section: Hybrid Organic-inorganic Lbl Coatingsmentioning
confidence: 99%
“…34 Since then, researchers have developed LbL FR coatings for textiles, [34][35][36] plastic plaques, [37][38][39] and polyurethane foam (PUF) 40,41 . The coatings were constructed of synthetic and bio-based polymer binders (e.g., polyacrylic acid and DNA), 42 and have contained a wide range of fire retardants and protective residue formers (e.g., montmorillonite clay, 16,33,34 silica, [43][44][45] α-M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT zirconium phosphate, 46 and carbon nanotubes and nanofibers [47][48][49].…”
Section: Introductionmentioning
confidence: 99%